An exploration of the impression management and dialogical potential of arts organisations - Angelique Nairn; Deepti Bhargava (Cogent Arts & Humanities)
Creating and maintaining mutually beneficial relationships between organisations and their publics is at the core of public relations practice. Social media has created new opportunities to nurture these relationships through mediated interactions. Ideally, if organisations and publics participate in these interactions with a dialogic orientation, they are likely to have an authentic relationship.Arts organisations globally, however, are known to utilise public relations more as a way of managing impressions, promoting the experiential nature of their creative products, and garnering ticket sales. We, therefore, conducted a thematic analysis to examine if this was also the case with a New Zealand arts organisation.On examining New Zealand Opera’s Facebook™ posts and their accompanying comments; this study found that social media was only being used for one-way impression management, without any dialogic intention to stimulate the public into authentic engagement.